Staphylococcus aureus Dormancy: Waiting for Insurgency - Nasser, Ahmad; Jahanbakhshi, Shiva; Soltan Dallal, Mohammad M.; Banar, Maryam; Sattari-Maraji, Azin; Azimi, Taher (Current Pharmaceutical Biotechnology, 2023)
Relapse infection usually results from resistance to the antibiotic, acquired genes, or persister cells. Persister cells are formed through mutation, reduced activity or metabolically inactive pathways induced by antibiotics, harassing conditions, low ATP, and malnutrition. These factors provide the ground for bacteria to grow slowly. Such a slow growth rate makes traditional antibiotics ineffective against persister cells. Staphylococcus aureus (S. aureus), in addition to this form, can be observed in Small Colony Variants (SCVs), L-forms, and dormant, all of which are characterized by at least one feature, i.e., slow growth. Despite their slow growth, they are metabolically active in terms of stringent SOS and cell wall stress responses. The stress response involves resistance against harassing conditions, and it survives until it is reactivated later. The present study aims to discuss the mechanisms of all persister cell formations, circumstances involved, gene mutation, and adoptable strategies against it.
Keywords: biofilm